If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4 = 2(8 + -6x) Reorder the terms: 4 + 2x = 2(8 + -6x) 4 + 2x = (8 * 2 + -6x * 2) 4 + 2x = (16 + -12x) Solving 4 + 2x = 16 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 4 + 2x + 12x = 16 + -12x + 12x Combine like terms: 2x + 12x = 14x 4 + 14x = 16 + -12x + 12x Combine like terms: -12x + 12x = 0 4 + 14x = 16 + 0 4 + 14x = 16 Add '-4' to each side of the equation. 4 + -4 + 14x = 16 + -4 Combine like terms: 4 + -4 = 0 0 + 14x = 16 + -4 14x = 16 + -4 Combine like terms: 16 + -4 = 12 14x = 12 Divide each side by '14'. x = 0.8571428571 Simplifying x = 0.8571428571
| 5x-2=3(2x+7) | | x+2x+24=180 | | -2x+4=4-2x | | -5x+3=-5x+4 | | 42+6x=100-2x | | 36=12+(15t)-6 | | 3x+1+x+21=180 | | 90+2x+2+x+11=180 | | 4(x+2)=10 | | a^2+b^2=243 | | a^2+b^2=34 | | a^2+b^2=27 | | (5)(12)+3(-9)=33 | | (5)(12)+3(-9)= | | 2x-13=x+3 | | X^2+4=12 | | 12x-(4x-8)=32 | | x^2-14x-21=0 | | 3x+19=7x-5 | | (-2)3x-3= | | 6-10=-10-6 | | 5-7=5+-7 | | x(x+1)(x-1)(x+2)-24=0 | | x-0.1x=20 | | x-0.2x=20 | | 12/10-3/5+2/15= | | 3/8-2/8= | | 7(y-5)/4=-4y | | 3(6x-7)+7=18x-14 | | 6x-5=3x-7 | | -2(3x-1)=3x | | 3p+5=7p-15 |